From Scratch? About three attempts to build an appropriate university campus in Yekaterinburg - Bagina, Elena (project baikal, 2015)
In 2013 the foundation stone of a new campus of Ural Federal University was laid in the area of the lakes Shartash and Malyi Shartash. In 2016 its first stage will be put in commission. Construction started despite all compelling comments from ecologists, sociologists, transport specialists and architects. The architecture of premises also triggers a lot of questions among specialists. Building of the new UrFU campus “from scratch” is the third attempt within 100 years to create a student campus in Yekaterinburg (Sverdlovsk) by examples from the West. The first attempt to build the Mining Institute was a failure because of the revolution of 1917. Realization of the Ural Polytechnic Institute campus took 20 years. The future of the new UrFU campus is uncertain, but the construction is going ahead at full speed.